2007
DOI: 10.1080/08958370701492706
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Studies on the Effects of Controlled Exposure to Fine, Coarse and Ultrafine Ambient Particulate Matter from a Single Location

Abstract: Particle size has been implicated by epidemiological and toxicological studies as an important determinant of the toxicity of ambient particulate matter (PM). In an effort to characterize the cardiovascular, hematological and pulmonary effects of different PM size fractions in humans, we have conducted controlled human exposures of normal volunteers to ultrafine-, fine- and coarse- fraction PM concentrated from ambient air in Chapel Hill, North Carolina. Healthy non-smoking male and female subjects between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 21 publications
3
37
2
Order By: Relevance
“…In many of these single-episode short-term exposures, no overt changes in plasma cytokine levels were observed after CAP [381][382][383] or diesel exhaust. 345,384 -386 Similarly, CRP levels have not consistently been found to increase in the time frame and context of most of these studies.…”
Section: Systemic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In many of these single-episode short-term exposures, no overt changes in plasma cytokine levels were observed after CAP [381][382][383] or diesel exhaust. 345,384 -386 Similarly, CRP levels have not consistently been found to increase in the time frame and context of most of these studies.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Serum amyloid A and the ratio of factor VIII to von Willebrand factor, an indicator of an increased risk of venous thromboembolism, were increased at 4 hours after exposure. 395 Samet et al 383 reported an association between various coagulation markers and exposure to ultrafine, fine, and thoracic coarse CAP among healthy young adults. Although exposure to coarse CAP did not result in significant changes in hemostatic variables, the overall trend suggested a prothrombotic effect.…”
Section: Thrombosis and Coagulationmentioning
confidence: 99%
“…The authors are not aware of any published human inhalation studies using iron oxide nanoparticles. However, several controlled human inhalation studies have exposed volunteers to other ultrafine particles [57][58][59][60][61][62][63][64][65][66]. In addition, many human inhalation studies have been conducted using Technegas or 99m Tc labeled ultrafine carbon particles; however, this literature is beyond the scope of this review.…”
Section: Controlled Human Volunteer Inhalation Studiesmentioning
confidence: 87%
“…26 Healthy human subjects exposed to concentrated ambient particles developed pulmonary inflammation characterized by increased presence of inflammatory cells and alterations in IL-8 expression in the lung lavage fluid. 27,28 Similarly, human subjects exposed to diesel particulates, a major component of ambient PM, developed neutrophilic airway inflammation and increased IL-8 expression and had altered levels of oxidative stress markers myeloperoxidase and reduced glutathione and urate. 29 Allen and colleagues measured an association between ambient PM exposure and significant alterations in inflammatory (exhaled NO) and lung-function measurements in children.…”
Section: Ambient Air Pollutionmentioning
confidence: 99%